Distinct oral DNA viral signatures in rheumatoid arthritis: a Pilot study - Mahin Ghorbani; Nooshin Khoshdoozmasouleh (Journal of Oral Microbiology)
Background Despite evidence linking viruses and oral microbiome to rheumatoid arthritis (RA), limited whole genome sequencing research has been conducted on the oral virome (a viral component of the microbiome) of untreated RA patients. This pilot research seeks to address this knowledge gap by comparing the oral virome of untreated rheumatoid arthritis patients (RAs) and healthy individuals (HCs).Method Whole genome DNA sequence of saliva samples from 45 participants including 21 RAs and 24 age and gender matched HCs was obtained from the BioProject: PRJEB6997. Metaphlan3 pipeline and LEfSe analysis were used for the viral signature detection. Wilcoxon pairwise test and ROC analysis were used to validate and predict signatures.Results RA exhibits higher alpha diversity compared to HCs. Callitrichine gammaherpesvirus 3, Human gammaherpesvirus 4 (EBV), Murid betaherpesvirus 8, and Suid alphaherpesvirus 1 were enriched in RAs, while Aotine betaherpesvirus 1 from the Cytomegalovirus genus was enriched in HCs. In addition, Saccharomyces cerevisiae killer virus M1 (ScV-M1) was found to be enriched in RAs, whereas bacteriophage Hk97virus (Siphoviridae) and Cd119virus (Myoviridae) were enriched in HCs.Conclusion This study identifies significant DNA oral viral signatures at species level as potential biomarkers for the early detection and diagnosis of rheumatoid arthritis.